Calcium signaling regulates apoptosis-induced proliferation in Drosophila - Suthar, Komal Panchal; Hounsell, Caitlin; Fan, Yun; Bergmann, Andreas (PLOS Biology, 2026)
Caspases, traditionally viewed as mediators of apoptosis and tumor suppressors, have also been shown to promote cell proliferation and to contribute to tumor growth. For example, the initiator caspase Dronc (the Drosophila orthologue of Caspase-9) can trigger apoptosis-induced proliferation (AiP), a process where apoptotic cells generate mitogenic signals for compensatory proliferation independently of their apoptotic function. AiP is crucial for homeostatic cell turnover, wound healing, and tissue regeneration. Previously, we established that Dronc activates the NADPH oxidase DUOX at the plasma membrane, resulting in the production of extracellular reactive oxygen species (ROS) which are required for AiP. However, the mechanism by which Dronc activates DUOX has remained elusive. Here, we identified Dronc-dependent Ca2+ entry into the cytosol as a significant factor for DUOX activation and AiP. Three cell surface Ca2+ channels of the TRP family mediate Ca2+ influx in a non-redundant fashion. Additionally, calcium-induced calcium release (CICR) from the ER was identified as another source of cytosolic Ca2+ during AiP. Notably, DUOX itself acts as a Ca2+ effector in AiP, requiring Ca2+ binding for its activation. These findings highlight the importance of Ca2+ signaling in AiP and provide insights into how similar signaling mechanisms might operate in vertebrates.